2015
DOI: 10.1128/genomea.00194-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of NDM-5-Producing Escherichia coli Sequence Type 648 and Genetic Context of bla NDM-5 in Australia

Abstract: We report here the draft genome sequence of uropathogenic Escherichia coli sequence type 648 (ST648) possessing blaNDM-5 from a 55-year-old female in Australia with a history of travel to India. The plasmid-mediated blaNDM-5 was in a genetic context nearly identical to that of the GenBank entry of an IncX3 blaNDM-5 plasmid previously reported from India (Klebsiella pneumoniae MGR-K194).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…In K. pneumoniae plasmid pJEG027 (20), an IS5 family transposase truncates the ISAba125 and IS26 is found 2.189 kb downstream from the bla NDM-4 gene. A similar genetic structure is present in GenBank deposits KP826705 (unpublished) and KP178355 (21), containing, respectively, the bla NDM-7 and bla NDM-5 genes.…”
mentioning
confidence: 78%
“…In K. pneumoniae plasmid pJEG027 (20), an IS5 family transposase truncates the ISAba125 and IS26 is found 2.189 kb downstream from the bla NDM-4 gene. A similar genetic structure is present in GenBank deposits KP826705 (unpublished) and KP178355 (21), containing, respectively, the bla NDM-7 and bla NDM-5 genes.…”
mentioning
confidence: 78%
“…To date, several studies showed that bla NDM-5 was carried by IncX3 plasmids in China, 46,47 India, 48 Denmark 49 and Australia. 50 The fact that IncX-type plasmids have been shown to be conjugatable in most studies could explain the rapid spread of bla NDM-5 -carrying isolates. Therefore, it is imperative that feasible and effective measures are taken immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Their association with β-lactamases, such as the bla NDM , has described in K. pneumoniae, E. coli, and Providencia stuartii isolates from countries as diverse as India, Canada, Kenya, New Zealand, Australia, and the United States. [35][36][37] Although the contig bearing the A/C 2 replicase gene did not harbor the class 1 integrase and associated gene cassettes, we would not be surprised if further genomic sequencing proves this to be the case.…”
Section: Genomic Locationmentioning
confidence: 93%